2012 Eighth International Conference on Intelligent Environments 2012
DOI: 10.1109/ie.2012.39
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Complex Activity Recognition through Smart Phones

Abstract: Abstract-Due to an increased popularity of assistive healthcare technologies activity recognition has become one of the most widely studied problems in technology-driven assistive healthcare domain. Current approaches for smart-phone based activity recognition focus only on simple activities such as locomotion. In this paper, in addition to recognizing simple activities, we investigate the ability to recognize complex activities, such as cooking, cleaning, etc. through a smart phone. Features extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
155
1
19

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(190 citation statements)
references
References 15 publications
1
155
1
19
Order By: Relevance
“…It is challenging to objectively map the privacy concerns that may be associated with any particular sensor, since they can vary across users and strongly depend on what other data is available. For instance, gyroscope is typically used together with accelerometer to detect activities such as walking, standing, sitting and lying can be recognised with high accuracy 96% [3], while on the other hand complex activities (e.g., cooking, cleaning and sweeping) are still considered challenging to recognise [13]. Therefore, we rely on subjective assessment, heuristics, and our review of literature [19,22,28] to rate the privacy concerns for each sensor.…”
Section: Studymentioning
confidence: 99%
“…It is challenging to objectively map the privacy concerns that may be associated with any particular sensor, since they can vary across users and strongly depend on what other data is available. For instance, gyroscope is typically used together with accelerometer to detect activities such as walking, standing, sitting and lying can be recognised with high accuracy 96% [3], while on the other hand complex activities (e.g., cooking, cleaning and sweeping) are still considered challenging to recognise [13]. Therefore, we rely on subjective assessment, heuristics, and our review of literature [19,22,28] to rate the privacy concerns for each sensor.…”
Section: Studymentioning
confidence: 99%
“…They concluded that accelerometer and gyroscope complement each other in general, however magnetometer is not so promising due to its dependency on directions. Dernbach et al [29] investigated the ability to recognise not only locomotion activities, but also high level activities, such as cooking and cleaning. In general, the recognition accuracy using on-board sensors alone is lower than other approaches in which specific sensors are attached to targeted areas of human body.…”
Section: Smartphone Based Activity Recognitionmentioning
confidence: 99%
“…For example, the Opportunity Project has recorded a set of ADL in a sensor-rich environment using 72 environmental and body sensors. Similarly, other works have provided datasets such as [Tapia et al, 2006] and [Dernbach et al, 2012].…”
Section: Experimental Data Collectionmentioning
confidence: 99%